Comparative assessment of different ivermectin and doramectin formulations for mange control in grazing steers - Canton, Candela; Muchiut, Sebastian; Dominguez, María Paula; Lanusse, Carlos; Alvarez, Luis Ignacio; Lifschitz, Adrian (Elsevier, 2023)
Psoroptic mange causes relevant losses of productivity in cattle. Macrocyclic lactones are one of the main pharmacological tools recommended for controlling it. The aim of the current work was to compare the relationship between the pharmacokinetic behavior and the effectiveness of both ivermectin (IVM) and doramectin (DRM) following their administration as either the traditional (1 %) or long-acting (3.15–3.5 %) injectable formulations to cattle naturally infected with Psoroptes ovis. The overall work involved three trials (1, 2 and 3) carried out on commercial beef cattle farms (grazing systems). In Trial 1, 20 grazing steers with active mange infection were allocated into 2 groups (n = 10) and treated subcutaneously (SC) with either IVM (1 %) or DRM (1%) at 0.2 mg/kg. In Trial 2, 16 grazing steers with active mange divided in 2 groups (n = 8) were treated SC with either IVM 1 % (0.2 mg/kg) or IVM 3.15 % long-acting (0.63 mg/kg). In Trial 3, 2 groups of mange infected steers (n = 8) were treated SC with either IVM 3.15 % (0.63 mg/kg) or DRM 3.5 % (0.7 mg/kg). Blood samples were collected of each experimental group and the drug systemic availability was estimated by measuring of IVM/DRM concentrations by HPLC. Skin scraping samples were collected from each animal and mites were counted at 14, 21 and 28 days post-treatment. In Trial 1, the mite density score on day 14 was significantly lower for DRM (0.60) compared to IVM (1.80) (P = 0.019). Based on the number of animals clinically cured (negative to the presence of mites), the efficacy of DRM was higher (80 %) than that obtained for IVM (10 %) (P < 0.05). DRM systemic exposure measured as AUC was 1.37-fold higher compared to IVM. In Trial 2, even though IVM exposure was significantly greater after the long-acting (3.15 %) compared to the traditional formulation (1 %), none of the treatments significantly reduced the mite density score, with a percentage of animals cured between 0 % and 37.5 % after both IVM treatments. In Trial 3, the 100 % of cured animals were achieved at day 21 (IVM 3.15 %) and at day 28 (DRM 3.5 %) post-treatment. In conclusion, DRM treatment could offer some therapeutic advantages in field situations where IVM fails to control mange. Depending on the level of susceptibility of the mite population, long-acting pharmaceutical formulations can be useful to control Psoroptic mange in cattle. The use of macrocyclic lactones for mange control in cattle should be based on appropriate diagnosis on each individual farm.